High thermal stability of submicron grained Cu processed by asymmetrical rolling. (5th September 2016) - Li, Wei; Shen, Yao; Xie, Chaoying
Abstract: In this paper, we report the microstructure evolutions of symmetrically and asymmetrically rolled Cu at different temperatures, and reveal an important role of asymmetry induced microstructure homogeneity and removal of local severely distorted structures on the enhancement of thermal stability. With the same total reduction of 90%, two kinds of submicron grained (SMG) Cu were processed by symmetrical and asymmetrical rolling respectively. The temperature dependent boundary spacing curves show the asymmetrically rolled Cu has significantly higher thermal stability, with the onset temperature of obvious grain coarsening being 40 °C higher than that for symmetrical rolled Cu. The enhanced thermal stability of asymmetrically rolled Cu can be attributed to the retardation of nucleation mainly realized by the improvement in microstructure homogeneity and the removal of local severely distorted structures. Our results demonstrate the feasibility of using asymmetrical rolling to improve the thermal stability of bulk SMG metals. Graphical abstract: Highlights: Deformed copper with a high thermal stability was processed by asymmetrical rolling. The high thermal stability is mainly attributed to the microstructure homogeneity. The asymmetry induced shear strain might be related to the structure homogeneity.